Oro-facial-digital syndrome type I: a case report with novel features - Shaheen Syed; Poonam Ramnath Sawant; Anita Spadigam; Anita Dhupar (University of São Paulo, 2021)
Oro-facial-digital syndrome is a group of rare heterogeneous hereditary disorders characterized by abnormalities of the oral cavity, face and digits, along with varying degrees of mental retardation. Currently, Oro-facial-digital syndrome has been classified into 14 types and two additional unclassified variants have been proposed. Amongst the various variants described, Oro-facial-digital syndrome type I is the most common. We report an interesting subclinical sporadic case of Oro-facial-digital syndrome type I in a 21-year-old female patient. Interestingly, our patient presented with a few novel hitherto unreported clinical findings like midline pits in the philtrum area and a hamartomatous proliferation of tissue in the anterior maxillary alveolar gingival region. This case report highlights the importance of prudent histopathological-clinical correlation, which can direct the flow of clinical investigations leading to the detection and diagnosis of unsuspected conditions as learned in this case. We would also like to emphasize that comprehensive examination of new born for structural abnormalities of the orofacial region is crucial to early diagnosis of syndromes and subsequent referral for further evaluation and management.